Entre notícias : afetos e (re)sentimentos políticos nas páginas de O Matto-Grosso (1918-1935) - Sousa, Sandra Miria Figueiredo (2024)
ABSTRACT: This thesis had, as its source and object, the study O Matto-Grosso (OMT), a periodical circulated in Mato Grosso, Cuiabá, between 1879 and 1935. Due to its long circulation, the timeframe was limited to the period between 1918 and 1935. The initial milestone relates to the conciliation government of Dom Aquino Corrêa, in 1918, and its final chronological milestone is justified by the fact that it was the year that marked the interruption of the publication of the periodical, after the death of its owner, Emílio Calháo. Based on the OMT newspaper, this study intended to analyze the relations between the Cuiabá press and the Mato Grosso party politics. The theoretical-conceptual reflections on passions and political (re)feelings supported the analysis carried out and the use of the concept of representations. With this, the aim was to demonstrate that party politics, its backstage, its disputes, and betrayals impregnated the pages of the newspaper and were constitutive of its formation and history. Therefore, it is argued that political (re)feelings and passions transpired in the pages of this periodical, profoundly marking its production in contrast with other printed publications, parties, and politicians of the period, as well as its editorial position on Cuiabá. It is hoped that this thesis will contribute to future works that may be produced in the field of political history and to studies concerned with the history of the Brazilian press.